2014
DOI: 10.1007/s10554-014-0449-1
|View full text |Cite
|
Sign up to set email alerts
|

Tissue doppler myocardial performance index in patients with heart failure and its relationship with haemodynamic parameters

Abstract: The myocardial performance index (MPI) reflects both the systolic and diastolic function of the heart, and is easily applied in practice. In this study, we aimed to determine the relationship between MPI and invasive haemodynamic parameters in heart failure patients. A total of 126 patients with heart failure were selected, all of whom were referred for diagnostic cardiac catheterisation, and were divided into two groups. Group I consisted of 59 patients (32 men and 27 women, mean age 61 ± 10; functional capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…The MPI which reflects both the global; systolic and diastolic, function of the heart[ 13 ] was significantly higher in cases than controls denoting global cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MPI which reflects both the global; systolic and diastolic, function of the heart[ 13 ] was significantly higher in cases than controls denoting global cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…TDI showed no significant difference between compensated and decompensated cirrhotic patients; a finding that was also reported by other investigators. [ 13 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…The Tei index, also known as the myocardial performance index, is used to evaluate cardiac function on echocardiography 21 . This parameter has been used as a reliable parameter that is easy to obtain, which shows systolic and diastolic myocardial performance together and becomes more important when it is considered that it is affected by both diastolic and systolic function in a manner directly proportional to the isovolumetric contraction time and isovolumic relaxation time and is inversely proportional to the ejection time 22 . The Tei index is unaffected by age, heart rate, blood pressure, or preload, and it contains both systolic and diastolic components; therefore, it is an ideal indicator of changes in overall ventricular systolic and diastolic function 23 , 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial Performance Index (MPI/Tei index) is defined as the ratio of isovolumetric contraction time plus isovolumetric relaxation time to the ejection time and has found to be increased in heart failure patients [47]. It has also been shown to be an early marker of systolic or diastolic dysfunction [48,49] and correlates with disease severity [50] and adverse prognosis [51,52]. TDI-derived Tei index is considered more reliable and reproducible than that calculated using pulse-wave Doppler to assess global cardiac function [50].…”
Section: Cirrhotic Cardiomyopathy Diagnostic Approach With Echocardiomentioning
confidence: 99%
“…It has also been shown to be an early marker of systolic or diastolic dysfunction [48,49] and correlates with disease severity [50] and adverse prognosis [51,52]. TDI-derived Tei index is considered more reliable and reproducible than that calculated using pulse-wave Doppler to assess global cardiac function [50]. This index has been assessed in few studies with cirrhotic patients and has been demonstrated to be related with cirrhosis severity and brain natriuretic peptide (BNP) levels [53,54].…”
Section: Cirrhotic Cardiomyopathy Diagnostic Approach With Echocardiomentioning
confidence: 99%